Family punishment in Nazi Germany : sippenhaft, terror and myth - Loeffel, Robert (Palgrave Macmillan, 2012)
"In the Third Reich, political dissidents were not the only ones liable to be punished for their crimes. Their parents, siblings and relatives also risked reprisals. This concept - known as Sippenhaft - was based in ideas of blood and purity. This definitive study surveys the threats, fears and infliction of this part of the Nazi system of terror"--(Provided by publisher.)